PEMBELAJARAN KIMIA BERBANTUAN MULTIMEDIA UNTUK SISWA TUNARUNGU SMALB-B - Sri Poedjiastoeti; Liliasari Liliasari (Universitas Negeri Malang, 2016)
Development of Multimedia Aided Chemistry Instruction For Hearing Impairment Senior High School Students. This study aimed to develop multimedia on "compound" topic, supplemented with student worksheets. It was implemented in chemistry instruction in Senior High School for students with hearing impairment. Multimedia prototype was produced as instructional CD; the visual presentation used total communication in text, graphic, video, animation, and sign language; with interactive and tutorial system. Four students with hearing impairment were involved as the subjects. The usage of multimedia as intervention and the target behavior was concept understanding, with visual analysis data for base-line and intervention conditions. The results showed the increasing trends from base-line to intervention conditions and these never overlapped to each other. It could be concluded that aided multimedia in chemistry instruction was effective for students with hearing impairment.   Pembelajaran Kimia Berbantuan Multimedia untuk Siswa Tunarungu Smalb-B. Penelitian ini vertujuan mengembangkan multimedia topik "Senyawa" dilengkapi LKS dan diimplementasikan pada pembelajaran kimia. Prototipe multimedia: CD pembelajaran, visualisasi komunikasi total (komtal) dalam bentuk  teks, grafis, video, animasi, dan berbagai bahasa isyarat, dengan sistem tutorial dan interaktif. Penelitian menggunakan Single Subject Research dengan subjek  empat  siswa tunarungu SMALB-B. Penggunaan multimedia sebagai intervensi dan perilaku yang diharapkan adalah pemahaman konsep. Pemahaman konsep kondisi base-line dan intervensi dianalisis dengan analisis data visual dalam dan antar kondisi. Kecenderungan meningkat antara kedua kondisi dengan prosentase tumpang tindih 0%. Dengan demikian dapat dikatakan penggunaan multimedia berpengaruh baik pada pemahaman konsep siswa.